Incidencia de la lectura de los libros álbum de autores ecuatorianos, en el desarrollo de lenguaje en los niños y niñas de 4 a 5 años de edad del centro educativo Leopoldo Chávez del cantón Cascales de la provincia de Sucumbíos en el periodo lectivo 2014 – 2015. Lineamientos alternativos - López Macas, Elena Raquel (2016)
The present investigation was made in a analytical study, descriptive and explanatory of “LA LECTURA DE LOS LIBROS ÁLBUM DE AUTORES ECUATORIANOS, EN EL DESARROLLO DE LENGUAJE EN LOS NIÑOS Y NIÑAS DE 4 A 5 AÑOS DE EDAD DEL CENTRO EDUCATIVO “LEOPOLDO CHÁVEZ” DEL CANTÓN CASCALES DE LA PROVINCIA DE SUCUMBÍOS EN EL PERIODO LECTIVO 2014-2015”. LINEAMIENTOS ALTERNATIVOS, the same that was developed according to the Rules of Procedure of the academic regime of the National University of Loja. The central problem of my research is given with the following question: In what way affects the use of books album in the development of language in the boys and girls of 4 to 5 years of age of the Educational Center "Leopoldo Chavez of the Canton Cascales of the province of Sucumbíos in the academic year 2014-2015? For framing the way forward and address the research process is raised as a general objective: to investigate how affects the reading of books album of authors Ecuadorians, in the development of language in the boys and girls of 4 to 5 years of age of the Educational Center "Leopoldo Chavez" of the canton Cascales, Sucumbíos province. Academic Year 2014-2015. The methods used were: the scientific method, Inductivo-Deductivo, descriptive and analytic-synthetic, through which it was able to collect the bibliographic information and necessary and important field in this research process to then be analyzed and eventually result in the document order of diploma, allowing the collection of comprehensive information on the book album that underpin assertively the theoretical framework. The implementation of the survey to the teachers concludes that: a high percentage of female teachers are unaware of the importance and usefulness of the book album in the development process of the oral language of boys and girls. According to the observation guide, it is concluded that: In the proposed activities, based on the skills programmed in the initial education curriculum, they have not been able to acquire the skills that focus on the development of language such as orally describing graphic and digital images, structuring More elaborate sentences that describe objects that observe or tell a story based on their images from the cover and following the sequence of the pages Allowing us to show that there is a close relationship between the lack of implementation of motivating strategies such as the use of Book album in children's language development. It is recommended that teachers apply the guide to animation and reading induction, in addition to self - training on the importance and use of books in the language of the book, valuing permanently to implement in a timely manner the necessary changes.